Perancangan Sistem Pendukung Keputusan Pemilihan Alat Musik Drum Berkualitas dengan Menggunakan Metode Weighted Product - Fajar Ramadhan; Rismayanti Rismayanti (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
The rapid development of information technology has had a significant impact on various aspects of life, including the decision-making process that requires precision and objectivity. One of the problems often faced is product selection with various complex criteria, for example in selecting a quality drum. Drums as a percussion instrument have many variations in terms of sound quality, material, design, price, and durability, so a system is needed that can assist users in making a more rational choice. This study aims to develop a website-based Decision Support System (DSS) using the Weighted Product (WP) method to provide recommendations for drum selection. The WP method was chosen because it is able to perform calculations by considering the weight of each criterion so that the recommendation results are more objective. The system implementation is carried out through the design of a user-friendly web-based interface, making it easier for users to access, compare alternatives, and obtain recommendations without having to perform manual assessments that are time-consuming and potentially subjective. System testing was carried out by comparing the results of the system's recommendations with expert assessments, which obtained an accuracy level of 95%. These results indicate that the developed system has a high level of reliability and is suitable for use as an aid in decision-making in selecting quality drums. With this system, it is hoped that users, both beginners and professionals, will find it easier to choose drums that suit their needs and preferences.